Syntax of Testimony: Indexical Objects, Syntax, and Language or How to Tell a Story Without Words - von Heiseler, Till Nikolaus (Frontiers in Psychology, 2019)
Language––often said to set human beings apart from other animals––has resisted explanation in terms of evolution. Language has two fundamental and distinctive features: syntax and the ability to express non-present actions and events. We suggest that the relation between syntax and representation can be analyzed as a relation between structure and function. The structure allows expression of an infinite number of propositions using finite means (productivity). Thus it is possible to refer e.g. to who did what to whom. The strategy of the paper is to ask if there is evidence of any pre-linguistic kind of communication that fulfills the function of communicating an absent action. We identify a structural similarity between understanding indexes of past actions or events and linguistic syntax. For instance, when a human being infers past events from an index (i.e. a trace, the conditions of a conspecifics or an animal, a constellation or an object) the interpreters' comprehension must rely on concepts similar in structure and function to the ‘thematic roles’ believed to underpin the comprehension of linguistic syntax: in his or her mind the idea of a past action or event emerges along with thematic roles––like concepts; in the case of the presentation of e.g. a hunting trophy, the presenter could be understood to be an agent (subject) and the trophy a patient (direct object), while the past action killed is implied by the condition of the object and its possession by the presenter. We discuss whether both the presentation of a trophy and linguistic syntax might have emerged merely by having the same function (to represent a past action) or whether the presentation of an index of a deed could constitute a precursor of language. Both possibilities shed new light on early language use.